2004
DOI: 10.1007/s12126-004-1015-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging mothers and daughters: Relationship changes over time

Abstract: In the midst of health care crises involving older mothers and their adult daughters, health care professionals must attend to the significance of past roles and relationships of aging women. This article explores two concepts that influence aging mothers' and daughters' management of a health crisis. The two concepts, Internalizing Female Lineage and Evolving Matriarchs facilitate understanding of the complexities of the mother-daughter relationship over time. These concepts emerged from a grounded theory stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Building on Meleis's theory of transition [65] Byrne's study [31] identified several patterns within carers' transitions. Meleis et al's [65] notion of transitional experience was also helpful to explore aspects related to the patient-carer relationship after a hip fracture in Shawler's studies [34,35,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on Meleis's theory of transition [65] Byrne's study [31] identified several patterns within carers' transitions. Meleis et al's [65] notion of transitional experience was also helpful to explore aspects related to the patient-carer relationship after a hip fracture in Shawler's studies [34,35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Some carers experienced a positive feeling of closeness to their elderly parent through spending more time with them which allowed them to renew their connection and redefine their relationship with the awareness that they were in the last phase of life for example "it's a real gift that we have this time together" [35 p.162]. For others overcoming a health crisis together was a positive experience [35,36]. A sense of filial responsibility could also create anxiety for example: "if anything happens to him there's a little part of me that says 'You know it'll be your fault if you didn't ask those questions and deal with that.'…”
Section: I) Maintaining Relationshipsmentioning
confidence: 99%